Rheology and processing of UV‐curable textured alumina inks for additive manufacturing. Issue 5 (26th May 2021) - Rosenberger, Andrew; Ku, Nicholas; Vargas‐Gonzalez, Lionel; Alazzawi, Mustafa; Haber, Richard
Abstract: A UV‐curable resin containing alumina (Al2 O3 ) powder and platelets was developed and characterized using a proof‐of concept tape‐casting system and trialed on a commercially available 3D‐printing platform (Admatec Admaflex 130). The influence of solids loading and solids platelet fraction on resin viscosity and depth of cure was investigated. Resins containing up to 40 vol% solids loading at platelet fractions up to 50% were found to have sufficiently low viscosity for tape casting and cure depths ranging from 0.29 to 0.39 mm. Alumina platelets were observed to lower ink viscosity but also reduce shear thinning behavior compared to inks containing only powder. Printability of inks was assessed by layered tape casting, and verified with a trial build on an Admaflex 130. Due to the low solids loading of the resin, hot pressing at 1300°C and 66 MPa was employed to sinter specimens containing no platelets and 15% platelet fractions, yielding specimens with near theoretical densities (99.7%) and average grain sizes of 0.96 µm and 0.83 µm, respectively. Alignment before and after sintering was assessed by SEM and XRD, with lotgering factors of 0.045±0.005 and 0.114 measured in the green and sintered specimens, respectively.